The potential source of natural antioxidant agent of Casia alata microgreen - Novianti Adi Rohmanna; Ronny Mulyawan; Zuliyan Agus Nur Muchlis Majid (Agrovigor, 2023)
Commonly, plant was cultivated by microgreen have potentially source of natural antioxidant agents. This study was conducted to utilize Cassia alata (C. alata) as a microgreen and evaluated the potential of Microgreen gelinggang as the source of natural antioxidant agents. The seed of Cassia alata was cultivated in Rockwool at room temperature (27±1oC). At the appearance of the first true leaves, about 21 days, microgreens were harvested from a triplicate of trays with sterilized scissors. The antioxidant activity assay using the DPPH (2,2-difenil-1-pikrilhidrazil) radical scavenging activity method. It was analyzed using spectrophotometry UV-VIS. The result showed that the IC50 values of Microgreen gelinggang were 1.789x103 ±0.0  µg/mL. It was a weak category antioxidant. This study indicated that the extract of Microgreen gelinggang has a potential source of natural antioxidant agents.